Cardioprotection of Ginkgolide B on Myocardial Ischemia/Reperfusion-Induced Inflammatory Injury via Regulation of A20-NF-κB Pathway - Zhang, Rui; Xu, Lin; Zhang, Dong; Hu, Bo; Luo, Qi; Han, Dan; Li, Jiangbing; Shen, Chengwu (Frontiers in Immunology, 2018)
Inflammation urges most of the characteristics of plaques involved in the pathogenesis of myocardial ischemia/reperfusion injury (MI/RI). In addition, inflammatory signaling pathways not only mediate the properties of plaques that precipitate ischemia/reperfusion (I/R) but also influence the clinical consequences of the post-infarction remodeling and heart failure. Here, we studied whether Ginkgolide B (GB), an effective anti-inflammatory monomer, improved MI/RI via suppression of inflammation. Left anterior descending (LAD) coronary artery induced ischemia/reperfusion (I/R) of rats or A20 silencing mice, as well as hypoxia/reoxygenation (H/R) induced damages of primary cultured rat neonatal ventricular myocytes or A20 silencing ventricular myocytes respectively, served as MI/RI model in vivo and in vitro to discuss the anti-I/R injury properties of GB. We found that GB significantly alleviated the symptoms of MI/RI evidently by reducing infarct size, preventing ultrastructural changes of myocardium, depressing Polymorphonuclears (PMNs) infiltration, lessening histopathological damage and suppressing the excessive inflammation. Further study demonstrated that GB remarkably inhibited NF-κB p65 subunit translocation, IκB-α phosphorylation, IKK-β activity, as well as the downstream inflammatory cytokines and proteins expressions via zinc finger protein A20. In conclusion, GB could alleviate MI/RI-induced inflammatory response through A20-NF-κB signal pathway, which may give us new insights into the preventive strategies for MI/RI disease.